Decreasing effect of fluoride content in Antarctic krill (Euphausia superba) by chemical treatments. (4th February 2013) - Jung, Hae Rim; Kim, Min‐A; Seo, Yong‐Soo; Lee, Yang‐Bong; Chun, Byung‐Soo; Kim, Seon‐Bong
Summary Decreasing effects of fluoride contents in Antarctic krill (Euphausia superba) as affected by chemical treatments with and without heating were investigated. The used chemicals were NaOH, Na2CO3, Na2SO3, citric acid, acetic acid, phosphoric acid, HCl, ethanol, lysine, aminoguanidine, arginine, carnitine, betaine, and creatine. Fluoride contents per dry weight were 788 ± 10 mg kg−1 in the whole body of krill (WBK) and 294 ± 4 mg kg−1 in the peeled krill meat (PKM) respectively. When WBK was treated with chemicals with and without heating or thawed, fluoride was not decreased. On the other hand, when the PKM was treated with chemicals without heating was remarkably decreased to less than 100 mg kg−1, which is the criteria recommended by FDA. Particularly, the treatment of betaine without heating showed the best reduction effect of 30 ± 6 mg kg−1, followed by carnitine (38 ± 17 mg kg−1), acetic acid (52 ± 1 mg kg−1), phosphoric acid (67 ± 2 mg kg−1) and hydrochloric acid (68 ± 1 mg kg−1).